Legal Protection of Population Administration in The Recording of Deeds The Birth of A Street Child in Indonesia - Putri Hafidati (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
Population administration serve as protection, acknowledgment, quotation for Indonesian citizen personal status also legal status which regulated by Republic of Indonesia and 1945 constitution of Republic Indonesia. Birth Certificate is one kind of population administration which have to be given by the Country. More than 90% street children in big city as Bandung, Jakarta, and Tangerang doesn’t have birth certificate. House shelter in Tangerang city uncover the administration difficulty to gain a birth certificate for those street children. These street children were very vulnerable to violation of Human Rights. This is an descriptive-qualitative study. Primary, secondary and tertiary legal material were used for this Study purposes. This study show us that Indonesia haven’t fulfilled the legal protection for children rights. Keywords: Birth Certificate, Street Children, Child Identity